Individual differences in treatment effects of internet-based cognitive behavioral therapy in primary care: a moderation analysis of a randomized clinical trial - Karin Hyland; Danilo Romero; Sven Andreasson; Anders Hammarberg; Erik Hedman-Lagerlöf; Magnus Johansson (Addiction Science & Clinical Practice)
Abstract Background and aims Little is known regarding predictors of outcome in treatment of alcohol dependence via the internet and in primary care. The aim of the present study was to investigate the role of socio-demographic and clinical factors for outcomes in internet-based cognitive behavioral treatment (ICBT) added to treatment as usual (TAU) for alcohol dependence in primary care. Design Secondary analyses based on data from a randomized controlled trial in which participants were randomized to ICBT + TAU or to TAU only. Setting The study was conducted in collaboration with 14 primary care centers in Stockholm, Sweden. Participants The randomized trial included 264 adult primary care patients with alcohol dependence enrolled between September 2017 and November 2019. Interventions Patients in the parent trial were randomized to ICBT that was added to TAU (n = 132) or to TAU only (n = 132). ICBT was a 12-week intervention based on motivational interviewing, relapse prevention and behavioral self-control training. Measures Primary outcome was number of standard drinks last 30 days. Sociodemographic and clinical predictors were tested in separate models using linear mixed effects models. Findings Severity of dependence, assessed by ICD-10 criteria for alcohol dependence, was the only predictor for changes in alcohol consumption and the only moderator of the effect of treatment. Participants with severe dependence showed a larger reduction in alcohol consumption between baseline and 3-months follow-up compared to participants with moderate dependence. The patients with moderate dependence continued to reduce their alcohol consumption between 3- and 12-months follow-up, while patients with severe dependence did not. Conclusions Dependence severity predicted changes in alcohol consumption following treatment of alcohol dependence in primary care, with or without added ICBT. Dependence severity was also found to moderate the effect of treatment. The results suggest that treatment for both moderate and severe alcohol dependence is viable in primary care. Clinical trial registration: The study was approved by the Regional Ethics Board in Stockholm, no. 2016/1367–31/2. The study protocol was published in Trials 30 December 2019. The trial identifier is ISRCTN69957414, available at http://www.isrctn.com , assigned 7 June 2018, retrospectively registered.